High sensitive phosphorene and molecular imprinted polymers electrochemical sensor to determine benzene in oilfield-produced water - de Souza, João Carlos [UNESP]; Silva, João Pedro [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; de Andrade, Adalgisa Rodrigues [UNESP] (Elsevier, 2024)
A new electrochemical sensor based on a carbon screen-printed electrode (CSPE) modified with phosphorene (BP) and PEDOT:PSS (BP-PEDOT:PSS) and molecularly imprinted polymers (MIPs) composed of poly(o-phenylenediamine) has been developed and applied to determine low benzene concentrations in oilfield-produced water (OPW). Morphological and electrochemical characterization of the sensor confirmed that the CSPE surface was modified with BP-PEDOT:PSS and MIPs. CSPE modification with BP-PEDOT:PSS increased the electrochemical current by 24.8%. Under optimized conditions, the sensor presented analytical curves with two linear ranges from 4.0 × 10−8 to 1.0 × 10−7 mol L−1 and from 2.0 × 10−7 to 1.0 × 10−6 mol L−1. The limit of detection, limit of quantification, and sensitivity were 7.4 × 10−9 mol L−1, 2.3 × 10−8 mol L−1, and 36.4 A L mol−1 (n = 3), respectively. The sensor showed good interday and intraday repeatability, with RSD values of 3.4% and 4.9%, respectively. Its stability was excellent, preserving 90.7% of its initial current after storage at room temperature and in contact with the ambient atmosphere for 15 days. The sensor also displayed excellent selectivity for the benzene molecule in the presence of interferents (o-xylene, m-xylene, phenol, and toluene). The proposed method was validated by comparison using the technique of gas chromatography coupled to flame injection detection (GC-FID) and successfully applied to determine benzene in an OPW sample.
Keywords: Benzene; Electrochemical sensor; Molecularly imprinted polymer; Oil; Oilfield-produced water; Phosphorene